TRADITION OF RAJANG PRAYER OVERVIEW PERSPECTIVE OF ISLAMIC EDUCATION - Syafaruddin, Baso (Universitas Islam Negeri Alauddin Makassar, 2018)
Prayer is an inseparable part of humans, especially for Muslims, because prayer is the main weapon for a Muslim. God listens to the prayer of his servants both physical and spiritual. Tradition of physical prayer has many variations. One of them is the tradition of Rajang Prayers in the Lakadaung Village, Dua Limpoe, Maniangpajo Sub-District. Tradition is a series of together prayer activities to pray for the spirits of parents and ancestors. This is the duty of every child to pray for parents and ancestors who have died. As a form of appreciation for parents who have given birth and raised their children.Tradition of Rajang Prayer is a legacy that must be maintained and juxtaposed with Islamic education so that the activity can be of worship value to those who carry out and reward their parents and ancestors. This type of research is qualitative with data collection methods that are in-depth interviews, observation, documentation studies and reference tracing. After the data is collected then analyzed and tested the validity of the data.